A Discussion on Chronomedicine in the Treatment of Constipation Based on the Najia Method of Midnight-Noon Ebb-Flow Theory - Xiaoru Zhou; Jing Liu; Yaming Xu; Ruihui Wang (Medicine Insights, 2026)
This paper systematically discusses the diagnostic and therapeutic principles of applying chronomedicine to the management of constipation from the perspective of the Najia method of midnight-noon ebb-flow theory. Also known as biological clock therapy, chronomedicine employs midnight-noon ebb-flow acupuncture to select acupoints according to the diurnal waxing and waning of qi and blood as well as the opening-closing rhythm of meridians, serving as an important component of traditional Chinese medicine chronoacupuncture therapy. The Najia method matches the twelve meridians with the ten heavenly stems and calculates the timing for activating five-shu points based on the heavenly stems of days and hours alongside the generation sequence of the five elements. Compared with the Nazi method, it demonstrates superior efficacy in treating chronic disorders arising from long-term dysfunction of multiple zang-fu organs. Constipation is a prevalent digestive condition characterized by prolonged defecation intervals, dry stools, and straining during bowel movements. Its core pathogenesis involves impaired transportation function of the large intestine and obstructed fu-qi, frequently accompanied by disorders of qi, blood, and body fluid metabolism as well as dysfunction of multiple zang-fu organs. The fundamental therapeutic principles aim to unblock fu-qi and restore the intestinal transportation rhythm in accordance with natural circadian timing. Current clinical observations indicate that chronotherapeutic strategies guided by the Najia method, including timed acupuncture, timed auricular point stimulation, timed acupoint application, and timed herbal foot bath, can effectively improve defecation outcomes and achieve superior overall therapeutic efficacy compared with conventional non-timed approaches. As a carrier for chronomedicine, the Najia method provides novel therapeutic avenues for constipation management, facilitates exploration into the temporal pathogenesis of intestinal disorders, and merits broader application in primary clinical settings.